Analytical solutions of conformable advection–diffusion equation for contaminant migration with isothermal adsorption. (July 2020) - Yang, Shuai; Chen, Xiang; Ou, Lin; Cao, Yuan; Zhou, Hongwei
Abstract: Based on the conformable derivative approach, conformable advection–diffusion equations with equilibrium and non-equilibrium adsorption for contaminant migration in porous media are proposed, and the analytical solutions are obtained via the Laplace transform method in this work. In addition, concentration profiles are carried out for the illustrative explanations of the analytical solutions. This work forms a basis for further applications of conformable calculus in modeling of contaminant time-dependent migration in porous media.